Reduced Graphene Oxide Overlayer on Copper Nanocube Electrodes Steers the Selectivity Towards Ethanol in Electrochemical Reduction of Carbon Dioxide - Aguirre-Quintana, M; Aguirre-Quintana, M; Ruiz-Leon, D; Ruiz-Leon, D (John Wiley and Sons Inc, 2022)
Developing copper-based electrocatalysts that favor high-value multi-carbon oxygenates is desired, given their use as platform chemicals and as a direct fuel for transportation. Combining a CO-selective catalyst with copper shifts the selectivity of CO2 electroreduction toward C2 products. Herein, we developed a reduced graphene oxide (rGO)-modified copper nanocube electrocatalyst that could shift the selectivity of CO2 electroreduction towards ethanol (Faradaic efficiency 76. 84 % at −0.9 V vs. reversible hydrogen electrode (RHE)). Spectroelectrochemical Raman analysis reveals a higher population of *C2HxOy intermediates at −0.9 V vs. RHE on the rGO-modified copper nanocube electrocatalyst surface, which coincides with the highest faradaic efficiency of ethanol upon CO2 electroreduction at the same potential. Our results demonstrate that the rGO modification can enhance ethanol selectivity through a probable tandem electrocatalysis mechanism and provide insights into controlling electrocatalytic activity and product selectivity in the CO2 electroreduction reaction. © 2022 Wiley-VCH GmbH.